Prevention of taxane-associated acute pain syndrome with etoricoxib for patients with breast cancer: A phase II randomised trial. (August 2022) - Zhang, Junsheng; Gao, Hong-Fei; Yang, Ciqiu; Zhu, Teng; Ji, Fei; Yang, Mei; Zhang, Liulu; Li, Jieqing; Cheng, Minyi; Zhang, Tingfeng; Shen, Bo; Chen, Yuanqi; et al.
Abstract: Background: For patients with breast cancer who receive docetaxel chemotherapy, taxane-associated acute pain syndrome (T-APS), considered a form of neural pathology, is a significant clinical problem. We evaluated the effect of prophylactic etoricoxib on T-APS in patients with breast cancer. Materials and methods: We conducted a phase II randomised trial including 144 patients with breast cancer receiving four cycles of docetaxel-based chemotherapy. Patients were randomised in the ratio 1:1 to receive prophylactic etoricoxib (60 mg, Day 1 to Day 8) or no prophylactic treatment. The primary end-point was the overall incidence of T-APS across all cycles. Secondary end-points included the incidence of severe pain (greater than 5 on a scale 0–10); severity and duration of T-APS; Functional Assessment of Cancer Therapy-Breast subscale; chronic sensory and motor neurotoxicity and adverse events. Results: The overall incidence of T-APS across all cycles of chemotherapy in the etoricoxib group was 57.1%, while that in the control group was 91.5% (P < 0.001). The incidences of severe T-APS were 11.4% and 54.9% for the etoricoxib and control groups, respectively (P < 0.001). The mean Functional Assessment of Cancer Therapy-Breast subscale score of the etoricoxib group (103.79–107.24) was significantly higher than that of the control group (93.88–96.71) (P = 0.001 at cycle 1 and P < 0.001 at cycles 2–4). After four cycles of docetaxel chemotherapy, the etoricoxib group demonstrated a significantly higher mean Functional Assessment of Cancer Treatment Neurotoxicity subscale score than the control group (38.46, 95% CI: 37.63–39.29; 34.59, 95% CI: 33.73–35.45, respectively; P < 0.001). Electromyography showed that most peripheral sensory nerves in the etoricoxib group had significantly improved action potential amplitudes and conduction velocities compared with those in the control group. Conclusion: Prophylactic use of etoricoxib could significantly reduce the incidence and severity of docetaxel-induced acute pain syndrome and potentially decrease docetaxel-induced peripheral neuropathy. Trial registration: ClinicalTrials.gov, NCT04565600. Highlights: Prophylactic etoricoxib reduce the incidence of docetaxel-induced acute pain syndrome. Prophylactic etoricoxib may attenuate docetaxel-induced peripheral neuropathy. Supporting that acute taxane-induced pain syndrome is a form of nerve pathology.